Development of a Model to Predict Liver Decompensation prior to Transarterial Chemoembolization Refractoriness in Patients with Intermediate-Stage Hepatocellular Carcinoma - Ferreira-Silva,Joel (2023)
Abstract Introduction: Transarterial chemoembolization (TACE) is the first-line treatment for patients with intermediatestage hepatocellular carcinoma (HCC). For patients without an adequate response, current finding suggests that treatment with molecular target agents, approved for advanced stage, might present benefits. However, this requires a preserved liver function. This study aims to evaluate possible predictors of early deterioration of hepatic reserve, prior to TACE refractoriness, in a cohort of patients treated with TACE. Methods: Retrospective analysis of 99 patients with Child-Pugh class A and intermediate-stage HCC who underwent TACE as the first-line treatment. All patients were submitted to a bio-chemical and medical evaluation prior to initial TACE and every month afterward. Response to initial TACE was evaluated at 1 month. The time to Child-Pugh class deterioration before TACE refractoriness was assessed. Results: Ninetynine patients were included. Objective response rate (ORR) to initial TACE was assessed as present in 59 (63.4%) and as absent in 34 (36.6%) patients. Liver decompensated before TACE refractoriness in 51 (51.5%) patients, and the median time to liver decompensation was 14 (IQR 8-20) months after first TACE. In multivariate analysis, beyond up-to-7 criteria (HR 2.4, p = 0.031), albumin <35 mg/dL (HR 3.5, p < 0.001) and absence of ORR (HR 2.4, p = 0.020) were associated with decreased overall survival free of liver decompensation. Moreover, beyond up-to-7 criteria, albumin <35 mg/dL and absence of ORR associated negatively with 6-month survival free of liver decompensation. Our model created using those variables was able to predict liver decompensation at 6 months with an AUROC of 0.701 (p = 0.02). Conclusions: The absence of ORR after initial TACE, beyond up-to-7 criteria and albumin <35 mg/dL, was a predictive factor for early liver decompensation before TACE refractoriness in our population. Such patients might benefit from treatment escalation to systemic therapy, in monotherapy or in combination with TACE.